Free vibration analysis of multi-layered beam members including the effect of interlayer slip. (4th June 2010) - Inoue, Keiichi; Ishikawa, Koichiro
This paper is about the analysis of the free vibration of multi-layered beam considering interlayer slip. First, the equation of motion for the free vibration analysis of multi-layered beam members including the effect of interlayer slip is formulated by finite element method. Next, some results of numerical analyses are shown, and then, it is examined and considered the utility of this analytical technique.